(untitled) (Географический вестник=Geographical bulletin, 2017)
Рассмотрены вопросы, связанные с возможностью применения методов математического моделирования в гидрологических исследованиях. Обосновывается системный подход к математическому моделированию. THE SYSTEM APPROACH TO APPLICATION OF MATHEMATICAL MODELLING IN THE HYDROLOGY The questions connected with possibility of application of methods of mathematical modeling in hydrological researches are considered. The system approach to mathematical modeling is proved.